(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article emphasizes that every person has hidden creative abilities. And this creativity is intrinsically connected with art, painting, science, music. Creativity is the basis of each of these fields, and other disciplines are formed on their basis.